Literature Review : Sasaran Difusi Inovasi Dalam Lingkup Pendidikan Dasar - Eka Margareta Sinaga; KMS. Muhammad Amin Fauzi (UNIB Press, 2024)
In basic education, innovation diffusion is an important process that aims to introduce and adopt new ideas, practices or technologies to improve the quality of learning. This process involves stages ranging from the discovery of innovations, information dissemination, trial implementation, to the adoption or rejection of innovations by members of a particular social system. The diffusion of innovations in basic education is underpinned by several key concepts, including the diffusion process which includes the stages of innovation dissemination, factors influencing diffusion such as innovation characteristics and social context, and models of innovative implementation such as Roger's Diffusion of Innovations Model. Overall, the diffusion of innovations in basic education has great potential to improve the quality of education but its success depends on effective implementation and acceptance by all parties involved.